Antimicrobial Assessment and Phytochemical Screening of Medicinal Plants and Ganoderma lucidum. - Thapa, Rajat; Maharjan, Rashika; Tamang, Puja; Gautam, Priya; Adhikari, Rachana; Maharjan, Sandesh (International Journal of Applied Sciences and Biotechnology, 2022)
Nepal has always relied on traditional medicinal plants, herbs, and mushrooms that are locally available to treat numerous diseases. This study thus aimed to explore the antimicrobial properties of the plants and fungi that are commonly used as traditional medicines. Antimicrobial properties of 5 plants (Curcuma caesia. Acorus calamus, Moringa oleifera, Terminalia chebula, and Tinospora cordifolia) and 1 fungus (Ganoderma lucidum) were screened against 4 ATCC bacterial culture (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae). The extracts were prepared using Soxhlet’s apparatus in two solvents, i.e. ethanol and distilled water. Out of which, distilled water of Acorus calamus had the highest percentage yield. All extracts showed antimicrobial properties against S. aureus. The highest potential was observed in the ethanolic extract of Curcuma caesia against S. aureus with the zone of inhibition of 22mm The ethanolic extract of Tinospora cordiofolia showed promising antimicrobial against gram-negative bacteria: E.coli, P. aeruginosa and K. pneumoniae with the zone of inhibition 15mm, 15mm and 14mm respectively. The distilled water extract of Acorus calamus showed the highest antimicrobial activity against P. aeruginosa with a zone of inhibition of 18mm. In the case of phytochemical screening, both the extracts of Tinospora cordiofolia showed the highest phytochemicals (Terpenoids, Saponins, Coumarin, Flavonoids, Alkaloids, and Tannins). The experiment confirmed the efficacy of selected plants and fungus extract as a natural antimicrobial against all the test organisms used, suggesting the possibility of employing them in novel drug development against the treatment of infectious diseases caused by the test organisms.